Effect of two recombinant Trichinella spiralis serine protease inhibitors on TNBS-induced experimental colitis of mice. (23rd September 2018) - Xu, J; Wu, L; Yu, P; Liu, M; Lu, Y
Summary: Inflammatory bowel disease (IBD), which includes ulcerative colitis and Crohn's disease (CD), is a chronic autoimmune disease. Parasitic infections and their products have been shown to have protective effects on autoimmune diseases, including IBD. In this experiment, 96 male BALB/c mice aged 6–8 weeks were divided randomly into two large groups: prevention and therapy. The changes in the various indicators of colitis were detected to demonstrate that Trichinella spiralis serine protease inhibitors can relieve the inflammatory severity of 2, 4, 6-trinitrobenzenesulphonic acid solution (TNBS)-induced colitis and to explore possible immunological mechanisms. Results showed that the disease activity index (DAI) score, myeloperoxidase (MPO) activity, macroscopic and microscopic damage degrees of colon all decreased significantly, interferon (IFN)-γ expression decreased, interleukin (IL)-4 expression increased, nuclear factor kappa B (NF)-κB expression decreased and the percentage of CD4 + CD25 + forkhead box protein 3 (FoxP3 + ) regulatory T cells (Treg ) cells in the spleen. MLN increased significantly compared to the phosphate-buffered saline (PBS)/2, 4, 6-trinitrobenzenesulphonic acid solution (TNB) group. We found the same results with the T. spiralis Kazal-type serine protease inhibitors (TsKaSPI)+TNBS and TsAdSPI+TNBS groups in the large prevention group and the large therapy group, compared to the TNBS+PBS group with the TNBS+TsKaSPI and TNBS+TsAdSPI groups. Immunization with TsKaSPI and TsAdSPI on the CD models showed an intervention effect, possibly because TsKaSPI and TsAdSPI induced a T helper type 2 (Th2)-type immune response and balanced the TNBS-induced Th1-type immune response. Graphical Abstract: